2008
DOI: 10.1007/s00418-007-0373-8
|View full text |Cite
|
Sign up to set email alerts
|

Partial persistence of exercise-induced myocardial angiogenesis following 4-week detraining in the rat

Abstract: Enhanced angiogenesis, or capillary growth, has a prominent role among the various beneWcial eVects of exercise training on the myocardium. The aim of the present study is to assess if training-induced increases in capillarity and vascularization persist after 4 weeks of detraining. Adult male rats were trained to run on a treadmill for 10 weeks at »60% VO 2max , which did not induce cardiac hypertrophy, but increased (P < 0.05) the soleus/ body weight ratio, left ventricle capillarity and von Willebrand-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 37 publications
(43 reference statements)
6
37
0
Order By: Relevance
“…Our work showed complete regression of the analyzed data after just 2 weeks of detraining, contrasting with other studies (Craig et al 1991) which showed that the cardiac mass in rats regressed to baseline only after around 21 days of physical inactivity. Furthermore, a recent report (Marini et al 2008) found reversal to baseline values of LV capillarity and cell density, as well as upregulation of angiogenesis markers after 4 weeks of detraining. The higher tension in the T group indicates an enhancement of contractility, which can be attributed to several mechanisms, including increases on the activity of the Na + / Ca 2+ exchanger (Tibbits et al 1989), Ca 2+ ATPase of sarcolemma and sarcoplasmic reticulum (Pierce et al 1989;WisløV et al 2001), and sensitivity of the Ca 2+ myoWlaments (WisløV et al 2001).…”
Section: Variablesmentioning
confidence: 89%
“…Our work showed complete regression of the analyzed data after just 2 weeks of detraining, contrasting with other studies (Craig et al 1991) which showed that the cardiac mass in rats regressed to baseline only after around 21 days of physical inactivity. Furthermore, a recent report (Marini et al 2008) found reversal to baseline values of LV capillarity and cell density, as well as upregulation of angiogenesis markers after 4 weeks of detraining. The higher tension in the T group indicates an enhancement of contractility, which can be attributed to several mechanisms, including increases on the activity of the Na + / Ca 2+ exchanger (Tibbits et al 1989), Ca 2+ ATPase of sarcolemma and sarcoplasmic reticulum (Pierce et al 1989;WisløV et al 2001), and sensitivity of the Ca 2+ myoWlaments (WisløV et al 2001).…”
Section: Variablesmentioning
confidence: 89%
“…Although angiogenesis may not develop in Eur J Appl Physiol (2011) 111:859-868 865 short-term exercise , it may become critical in long-term training (Brown 2003;Laughlin et al 1998). In a previous work using a different set of animals, we reported that long-term low-intensity training increases capillary density and the number of von Willebrandt factorpositive cells, as well as gene expression of VEGF and its receptor KDR, but not of bFGF (Marini et al 2008). In HIGH-DET animals gene changes were reverted, while capillary density and the number of von Willebrandt factorpositive cells tended to return to basal (UNT) level (Marini et al 2008).…”
Section: Vegfmentioning
confidence: 94%
“…In a previous work using a different set of animals, we reported that long-term low-intensity training increases capillary density and the number of von Willebrandt factorpositive cells, as well as gene expression of VEGF and its receptor KDR, but not of bFGF (Marini et al 2008). In HIGH-DET animals gene changes were reverted, while capillary density and the number of von Willebrandt factorpositive cells tended to return to basal (UNT) level (Marini et al 2008). In principle, the lack of VEGF protein expression changes in the present study may stem from protein instability 24 h after the last training session, or it may reflect failure of training to accelerate angiogenesis.…”
Section: Vegfmentioning
confidence: 95%
See 1 more Smart Citation
“…Morphological methods were applied in numerous recent original papers to address a wide variety of topics in development, function and disease of the cardiovascular system (e.g., Schroeter et al 2007;Zaman et al 2007;Borisov et al 2008;Marini et al 2008). In an excellent review, Taatjes and colleagues highlighted the use and beneWts of microscopy imaging systems in conjunction with histochemical techniques in studies aimed at elucidating mechanisms underlying cardiovascular diseases at the cell and molecular level ("Imaging aspects of cardiovascular disease at the cell and molecular level"; Taatjes et al 2008a, b).…”
Section: Speciwc Applications Of Imagingmentioning
confidence: 99%